Дано:
F = 115 Н
s = 20 м
v = 6 м/с
v0 = 0
m - ?
При равноускоренном движении:
s = v0*t + a*t^2/2; т.к. v0 = 0, s = a*t^2/2
a = (v-v0)/t = v/t, откуда t = v/a
Подставляем: s = a * (v/a)^2/2 = v^2/(2*a), откуда a = v^2/(2*s)
По второму закону Ньютона: m = F/a
m =2* F*s /v^2
Подставляем:
m = 2*115*20/(8^2) ~72(кг.)
ответ:72кг.
Объяснение:
Дано:
F = 115 Н
s = 20 м
v = 6 м/с
v0 = 0
m - ?
При равноускоренном движении:
s = v0*t + a*t^2/2; т.к. v0 = 0, s = a*t^2/2
a = (v-v0)/t = v/t, откуда t = v/a
Подставляем: s = a * (v/a)^2/2 = v^2/(2*a), откуда a = v^2/(2*s)
По второму закону Ньютона: m = F/a
m =2* F*s /v^2
Подставляем:
m = 2*115*20/(8^2) ~72(кг.)
ответ:72кг.
Объяснение: